Pengaruh Kualitas Produk Dan Pelayanan Terhadap Kepuasan Konsumen Pada Depo Air Minum Isi Ulang Jayawater Di Tenggarong - Adawiyah, Raudatul (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2015)
The purpose of this study was to determine the influence of quality and service to customer satisfaction at refill drinking water depot Jaya Water Tenggarong and to know which variable has the most dominant influence on consumer satisfaction in drinking water refill depot Jaya Water Tenggarong. analysis model used for proving the hypothesis in this study is a quantitative analysis, the model of multiple regression analysis, the independent variable quality of the product (X1) and Services (X2). Then the dependent variable is customer satisfaction (Y). The regression equation generated through this research is Y = 4,278 + 0,444X1 + 0,287X2.In this study, researchers took population as an object of research is 30 respondents conducted during August 2014. From the results expressed that statement of the first hypothesis in the research which states that